Learning History Of Hindu-Buddha Removal To Invest In The Value Of Local Authenticity In The Middle School Students - Meli Febriani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Cultural relics in the Hindu-Buddhist era in the form of temples are part of local history that can provide positive values for students. The temple, which contains artifacts in the form of souvenirs, provides interesting local history material when it is explained with great inspiration by an innovative and creative teacher. This research was studied using a qualitative approach. The data collection process was carried out by means of observation, interviews, and document study. This research is aimed at seeing the importance of the legacy of a civilization, namely the temple, to be put forward in local history learning materials. This is a means for the formation of national identity through historical awareness and cultural awareness, as well as a teacher or teacher approach to introducing students to local wisdoms that exist around them. Learning like this will make students understand the history of themselves or their environment.